Guidelines for kidney cancer Part II: Assessment of renal cell cancer staging. Therapy - Szczylik, Cezary; Żołnierek, Jakub; Nurzyński, Paweł (Contemporary Oncology/Współczesna Onkologia, 2004)
In the case of renal cell cancer diagnosis the treatment is controversial. Many scientists claim that only surgery is the effective method of therapy. This article reviews proposed predictive and prognostic factors. It also discusses most common mutations of individual renal cancer types and pathological and clinical data which can have an influence on further diagnostic and therapeutic decisions. Factors which repeat in various classifications are the general status, levels of hemoglobin, calcium and lactate dehydrogenase. They make it possible to predict the patient's further condition and choose optimum therapy. The role of lung and bone metastases resection is undisputed. Systemic therapy of renal cell cancer is controversial. There is no convincing evidence that radiotherapy, chemotherapy or hormonotherapy is effective in the adjuvant treatment. Radiotherapy is a good choice in the case of bone and brain metastases treatment. Only immunotherapy was a breakthrough. Chemoimmunotherapy (interleukin-2, interferon, VBL, 5-fluorouracil) is the only effective therapy for metastatic renal cell cancer. New medicines such as Bay 43-9006, Bevacizumab, CCI-779 give hope for increasing the efficacy of the applied therapy.